Diversifikasi Produk Tempe Sanan Malang Melalui Pelatihan Pembuatan Model Dan Cetakan Tempe Karakter - Sumarwahyudi; Abdul Rohman Prasetyo; Triyono Widodo; E. Wara Suprihatin. D.P (Universitas Medan Area, 2023)
Kampung Sanan Malang has long been known as a center for making tempeh. It has been a long time since the Sanan Malang Tempe and Tempe Chips Production Center Association was established, which has 636 tempe producers as members. Some of its members have been able to process tempeh into various types of preparations. The innovation made in 2021 is named Character Tempe, namely tempeh in the form of animal characters, or fruits. During the trial period, character tempeh was produced using plastic cake molds. The problem faced is that members of this community want to be able to produce this tempeh with a larger production volume, and a more varied product. The reason is that no craftsmen have been able to make their own character models that are more varied as desired. Craftsmen also have not been able to make their own molds. The solution offered is training: making character models using plasticine, training on printing these models using RTV food grade. At the end of this activity, the craftsmen have the ability to produce processed tempeh characters quickly and with good quality so that they become a new Sanan Malang specialty product.